Determination of time-temperature superposition relationship of SBS modified asphalt based on special rheological phenomenon caused by SBS-formed structure in asphalt matrix. (10th November 2020) - Chen, Zihao; Zhang, Henglong; Duan, Haihui; Wu, Chaofan
Highlights: The presence of plateau region is influenced by time-temperature conditions. The type of plateau region varies according to SBS dosage in matrix. Equivalent time-temperature conditions can be obtained by plateau region of SBSMA. Abstract: The time-temperature equivalency theory is an important component in asphalt rheology and has been extensively applied in asphalt rheological characterization. The presence of phase angle plateau region shown by styrene–butadiene–styrene (SBS) modified asphalt binder are tightly related with time-temperature conditions, which can be utilized to develop a new potential method for determining time-temperature superposition relationship of SBS modified asphalt (SBSMA). In this paper, the relationship between SBS modifier dosage and its formed morphology structure in asphalt matrix was revealed by fluorescence microscope test. Then, the characteristics and the cause of rheological behaviors for SBSMA with different SBS dosages were described and analyzed, respectively. Further, in terms of different SBSMA binders, the specific ways to determine the time-temperature superposition relationship based on their respective special rheological phenomena were put forward and validated. The results indicate that the structures formed by SBS in asphalt matrix transform from dispersed phase to continuous phase as the SBS dosage increases. SBSMA binders with more than 2% dosage of SBS can all show plateau regions concerning phase angle, while the type of plateau region is varying for different SBS dosages. For SBSMA containing 4% dosage of SBS, the time-temperature conditions that correspond to the end point of every "concave" plateau region are equivalent. For SBSMA containing 6% and 8% dosage of SBS, time-temperature conditions that correspond to the middle point of "convex" plateau region are equivalent.